2020
DOI: 10.1002/smll.202003983
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework‐Derived Co3V2O8@CuV2O6 Hybrid Architecture as a Multifunctional Binder‐Free Electrode for Li‐Ion Batteries and Hybrid Supercapacitors

Abstract: Particularly, in lithium (Li)-ion battery (LIB) and supercapacitor (SC) applications, surface area and porosity properties of MOFs boost electrolyte uptake capability and shorten diffusion length. [4] Furthermore, the nanoscale voids in the MOF matrix alleviate severe volume fluctuations while performing electrochemical reactions. [5] Owing to these properties, the research community has been focused on the development of MOF-based/derived active materials to explore their applicability in the energy storage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Studies have shown that ternary metal oxides exhibit excellent electrochemical performance when used as supercapacitor electrode materials through the redox reaction between two different metal cations and the synergy between them [ 6 , 7 , 8 ]. As a transition metal element, vanadium has the characteristics of multivalent state (+2–+5) and easily deformable V-O polyhedron, which in turn produces a large amount of vanadium oxide compounds (M x V y O z ) [ 9 , 10 ]. The introduction of different types of metal ions M to M x V y O z can show different electrochemical properties, which provides a large number of options for the study of supercapacitors electrode materials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ternary metal oxides exhibit excellent electrochemical performance when used as supercapacitor electrode materials through the redox reaction between two different metal cations and the synergy between them [ 6 , 7 , 8 ]. As a transition metal element, vanadium has the characteristics of multivalent state (+2–+5) and easily deformable V-O polyhedron, which in turn produces a large amount of vanadium oxide compounds (M x V y O z ) [ 9 , 10 ]. The introduction of different types of metal ions M to M x V y O z can show different electrochemical properties, which provides a large number of options for the study of supercapacitors electrode materials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Furthermore, vanadium-based materials possess a relatively high chemical stability during the long-term chargestorage process because the binding force between vanadium and oxygen is very strong, while the oxidation state of vanadium is hard to convert to zero valence (vanadium metal). 23,24 In particular, Co 3 V 2 O 8 , as one kind of cobalt vanadate, features the typical crystalline structure related to a Kagome-staircase geometry and thus charge-storage superiority, leading to increased interest for its application in batteries and supercapacitors. 21,22 Fahimi et al synthesized a Co 3 V 2 O 8 hollow spheres cathode for supercapacitors, which showed a great specic capacity of 2376 F g −1 at 2 A g −1 and steady cycling performance.…”
Section: Introductionmentioning
confidence: 99%
“…25 Sekhar et al reported one metal-organic framework-derived Co 3 V 2 O 8 @CuV 2 O 6 nanorod composite, which exhibited excellent electrochemical properties in a lithium-ion battery (1089.3 mA h g −1 at 500 mA g −1 ) and supercapacitor (464.70 mF cm −2 at 4 mA cm −2 ). 24 As mentioned above, it would be meaningful to combine Ti 3 C 2 T x MXene with Co 3 V 2 O 8 by projecting the structure and components in order to acquire a much higher capacity and prolonged cycling stability. Ti 3 C 2 T x MXene bears high electron conductivity, excellent hydrophilicity, and mechanical exibility, which allow it to act as a preferable conductive matrix when coupled with a transition metal oxide to facilitate electron/ion transport at the contact interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] A plenty of MOFs-derived nanostructures such as carbon materials, [5][6][7][8] metal oxides, [9][10][11] metal chalcogenides, [12][13][14] and metal phosphides [15][16][17] have been fabricated. Among these derivatives, MOFs derived metal oxides (MMOs) have shown promising potentials in various applications, for example, electrocatalysis, [10,11] photocatalysis, [18,19] batteries, [20,21] and supercapacitors [9,22,23] A variety of MMOs have been fabricated with controlled nanostructures (e.g., hollow particles) by changing the calcination conditions (e.g., temperature, heating rate, atmosphere). [24][25][26][27][28][29][30][31][32][33][34] However, the direct calcination strategy is not applicable to all MOFs to prepare their corresponding MMOs with controllable morphologies, especially those with highly crystalline structures.…”
Section: Introductionmentioning
confidence: 99%